A reconceptualisation of native speakerism: ethnic return migrants and LOTE learning in South Korea. Issue 7 (9th August 2022) - Lee, Mun Woo
ABSTRACT: This study examines how Korean learners of Chinese perceive Chinese native speakerism, especially in relation to Choseonjok, or Korean-Chinese people. In-depth individual interviews were conducted with 47 Korean learners of Chinese who attended private Chinese language institutes or in-company Chinese programmes. The transcribed interviews were examined using grounded theory. The findings demonstrate that Chinese native speakerism in South Korea is highly contextualised and intertwined with notions of model pronunciation, ethnicity, nationality and identity. Most participants believed that the Chinese pronunciation of Choseonjok would be less standard than that of native Chinese speakers living in Beijing. Although the participants considered Choseonjok Chinese speakers to be less competent than native Chinese, they categorised Choseonjok as Chinese, pointing out that being able to speak Korean is not enough to become Korean, and that Choseonjok lack emotional loyalty towards Korea. The participants also considered Choseonjok to be unsuited to work as Chinese language teachers and more suited to certain jobs that Korean nationals avoid. This study critically demonstrates how native speakerism can be instantiated in accordance with sociocultural constructs and how this can contribute to a reconceptualisation of native speakerism, especially in a non-English case.